Brassinosteroids promote parenchyma cell and secondary xylem development in sugar beet (Beta vulgaris L.) root. (14th October 2021) - Wang, Wei; Sun, Yaqing; Li, Guolong; Zhang, Shaoying
Abstract: Increasing crop yield has always been an important goal in agriculture. Brassinosteroids (BRs) are growth‐promoting steroid hormones with vital roles in many root developmental processes. Sugar beet ( Beta vulgaris L.) is a root crop with a tertiary root structure. The differentiation of vascular bundles and the division of cambial cells increase root diameter. However, little is known about how BRs regulate the transverse growth of beetroot. Therefore, sugar beet with eight leaves was grown in medium containing epibrassinolide or brassinazole, an inhibitor of BR biosynthesis. BRs increased the spacing between the cambial rings by increasing the size of parenchyma cells between the rings and ultimately increasing root diameter. BRs also promoted secondary xylem differentiation. Moreover, the gene expression analysis of BvXTH33, BvSHV3, BvCESA6, BvPARVUS, and BvCEL1, which were related to the cell wall biosynthesis, indicated that BR could promote the growth of cell wall. These findings showed that BRs function in transverse development in beetroot.